EFFECTIVENESS OF BOARDS OF MANAGEMENT IN MANAGING PUBLIC PRIMARY SCHOOLS: A SURVEY OF KAHURO SUB COUNTY, MURANG’A COUNTY - Kariuki, Mburu Nicholas; Kathuri, Prof. Nephat J.; Mungai, Ms. Sarah (IJRDO - Journal of Applied Management Science, 2017)
A Board of management acts as a link between the school and the parents. It is supposed to giveschools leverage with regard to having the parents given a stake in the leadership and governanceof the schools. The study sought to find out the effectiveness of Boards of Management inKahuro Sub-County, Murang’a County. The study observed that: all the head teachersconsidered the Boards of Management to have been involved in the administration andgovernance programmes within the schools. All of the head teachers were of the view thatinvolvement of the schools management Boardmembers in financial management was enhanced.Furthermore they considered the BoM to have been involved in the supervision of teaching andlearning activities in their respective schools